2010
DOI: 10.1002/14651858.cd007868.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Fluoride toothpastes of different concentrations for preventing dental caries in children and adolescents

Abstract: BackgroundCaries (dental decay) is a disease of the hard tissues of the teeth caused by an imbalance, over time, in the interactions between cariogenic bacteria in dental plaque and fermentable carbohydrates (mainly sugars). The use of fluoride toothpaste is the primary intervention for the prevention of caries. ObjectivesTo determine the relative effectiveness of fluoride toothpastes of different concentrations in preventing dental caries in children and adolescents, and to examine the potentially modifying e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
162
0
24

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 347 publications
(210 citation statements)
references
References 104 publications
3
162
0
24
Order By: Relevance
“…Brushing teeth twice daily with the use of fluoride toothpaste at concentrations of 1000 ppm and above is recommended for children and adolescents [32]. In our study, only 41% of students brushed their teeth twice daily, and 91.9% of participants had no idea whether the toothpaste they use contain fluoride or not.…”
Section: Discussionmentioning
confidence: 54%
“…Brushing teeth twice daily with the use of fluoride toothpaste at concentrations of 1000 ppm and above is recommended for children and adolescents [32]. In our study, only 41% of students brushed their teeth twice daily, and 91.9% of participants had no idea whether the toothpaste they use contain fluoride or not.…”
Section: Discussionmentioning
confidence: 54%
“…the difference in caries increments between the treatment and control groups expressed as a percentage of the increment in the control group) of 10% [95% confidence interval (CI) 2% to 17%; p = 0.01] in favour of a combined regimen over toothpaste alone, but the statistically significant difference in favour of the combined use of fluoride-containing varnish and toothpaste accrued from a very small trial with a high risk of bias. A third Cochrane review 42 compared different concentrations of fluoride-containing toothpaste for preventing tooth decay in children and adolescents. This review included 79 trials on 73,000 children and confirmed the benefit of fluoride-containing toothpaste in preventing dental caries, but only for fluoride concentrations of 1000 parts per million (p.p.m.)…”
Section: Fluoride-containing Toothpastementioning
confidence: 99%
“…Five of the 60 reviews had been accompanied by a podcast and press release on publication. [71][72][73][74][75] These had all been picked up in the press with the number of mentions ranging from 37 to 100.…”
Section: Impact Of a Representative Sample Of Cochrane Systematic Revmentioning
confidence: 99%